Pengaruh Likuiditas Dan Profitabilitas Terhadap Pertumbuhan Laba Pada Perusahaan Teknologi - Keri Boru Hotang; Lia Astuti; Leandra Endhita Estuningsih (JURNAL AKUNTANSI DAN AUDIT TRI BHAKTI, 2023)
This research to examines the effect of Liquidity and Profitability on profit growth. The Liquidity is measured by the Current Ratio and the Profitability is measured by Return On Assets. The population of this research is all technology companies listed on the Indonesia Stock Exchange in the period 2017 – 2021. The approach used in this research is quantitative. Sampling in this study was carried out by purposive sampling method. The number of samples in this study are 9 technology companies listed on the Indonesia Stock Exchange in the period 2017 – 2021 with a total of 135 observations obtained. The analytical method used is multiple linear regression analysis using the SPSS (Statistical Product and Services Solutions) version 25. The results of this study indicate that (1) the Liquidity has a positive effect on profit growth. (2) Profitability ratios have a negative effect on profit growth.